PENGARUH PENAMBAHAN PROBIOTIK NITROGEN CYCLIC BACTERIA TERHADAP AKUMULASI AMONIA PADA BUDIDAYA IKAN NILA (Oreochromis niloticus) - Varadina Afifatunnisa; Alis Mukhlis; Laily Fitriani Mulyani (Universitas Mataram, 2026)
Intensive aquaculture of Nile tilapia (Oreochromis niloticus) frequently faces water quality deterioration problems due to ammonia accumulation from feed residues and fish metabolism. This study aimed to determine the effect and optimal dose of Nitrogen Cyclic Bacteria (NCB) probiotic on ammonia accumulation in Nile tilapia aquaculture. An experimental method with a Completely Randomized Design (CRD) consisting of 5 treatments and 3 replications was used, namely control (without probiotic) and probiotic addition at doses of 0.5, 1, 1.5, and 2 ml/L for 40 days. Parameters observed included growth, survival rate, and water quality, particularly ammonia. The results showed that probiotic addition significantly affected (p<0.05) fish growth, with the best dose at treatment D (1.5 ml/L), producing the highest absolute growth of 6.67 ± 0.32 g, relative growth of 46.70%, and daily specific growth rate of 0.96%/day. Survival rate was not significantly different among treatments (p>0.05), but tended to be higher in probiotic treatments compared to control. Ammonia content was not significantly different among treatments, but all values remained within the safe range (<0.1 ppm), with lower tendency at the highest dose (treatment E, 0.055 ppm). It was concluded that NCB probiotic can improve Nile tilapia growth and help maintain water quality, although its effect on ammonia reduction was not statistically significant.